Targeting the gut microbiome in the management of sepsis-associated encephalopathy - Barlow, Brooke; Ponnaluri, Sameer; Barlow, Ashley; Roth, William (Frontiers in Neurology, 2022)
Brain injury resulting from sepsis, or sepsis-associated encephalopathy (SAE), occurs due to impaired end-organ perfusion, dysregulated inflammation affecting the central nervous system (CNS), blood-brain barrier (BBB) disruption, mitochondrial dysfunction, oxidative stress, accumulation of toxic neuropeptides and impaired toxin clearance secondary to sepsis-induced hepatic and renal dysfunction. The gut microbiome becomes pathologically altered in sepsis, which likely contributes to the pathogenesis of SAE. Herein, we review the literature detailing dysregulation of microbiota-gut-brain axis (MGBA) in SAE and highlight potential therapeutic strategies to modulate the gut microbiome to mitigate sepsis-induced brain injury.